The Oldest Bryophyte Herbarium Specimens from Central Europe, Collected by M. E. Boretius in 1717: Taxonomy, Nomenclature, Datation and Ethnopharmacology - Jacek Drobnik; Adam Stebel; Maja Graniszewska (Plants, 2024)
The WA Herbarium at the University of Warsaw houses a collection of plants created in 1717 by Matthew Ernest Boretius. They were gathered in former East Prussia, near Angerburg, now Węgorzewo (Poland). It is the oldest plant collection from this part of Europe. Boretius compiled the herbarium as a collection of all the surrounding plants, but their folk names (Polish and German) recorded in the herbarium confirm the ethnobiological or ethnopharmaceutical importance of some species. We identified bryophyte species and checked the accuracy of their original identifications recorded in the herbarium. We provided their Latin (scientific, pre-Linnaean) nomenclature together with German and Polish vernacular names. We contextualised this information within the history of the medicinal use of bryophytes around 1717, when the plant collection was created. We also investigated whether the specimens could have come from Northeastern Poland. Mosses and liverworts from the herbarium were identified nomenclaturally (by means of their original scientific polynomial names written on herbarium sheets) and taxonomically. The herbarium holds two species and one subspecies of liverwort and 27 species and one variety of moss. The accuracy of the original identifications was assessed, with a particular focus on the species considered medicinal at the time. We found that bryophytes were poorly known in the time of Boretius, which was the last period in bryology before the introduction of magnifying devices into this science (this crucial step was made by Dillenius in 1741). The vernacular names used in the herbarium were recorded for Marchantia polymorpha and Polytrichum commune—the only two species with confirmed medicinal use by the year 1717.